Accounting for differences in risk of HCV re-infection by mental health diagnoses. (3rd June 2018) - Beaulieu, Tara; Barbic, Skye Pamela; Ti, Lianping
ABSTRACT: Introduction: There is widespread concern regarding the potential for hepatitis C virus (HCV) reinfection among key populations, particularly among people who inject drugs (PWID) and those living with a mental health condition. Area Covered: In this editorial we discuss the potential for specific mental health diagnoses (e.g., bipolar vs. substance use associated mania, vs. schizophrenia related disorders) to impact reinfection risk. This is an important consideration given distinct variations in risk behaviors for blood-borne virus infections (e.g., needle sharing) and patterns of health service use between diagnoses. Consideration of psychotropic agents may also have an effect on HCV reinfection given the supplemental influence of certain agents (e.g., typical antipsychotic drugs) on risk behaviours. Expert Commentary: An improved understanding of these effects may foster the beginning of a new era in the response to the optimal delivery of harm reduction programs and HCV care among PWID and those living with a mental health condition.